Β‐Ecdysone Augments Peak Bone Mass in Mice of Both Sexes. Issue 8 (August 2015) - Dai, Weiwei; Zhang, HongLiang; Zhong, Zhendong A.; Jiang, Li; Chen, Haiyan; Lay, Yu‐An Evan; Kot, Alexander; Ritchie, Robert O.; Lane, Nancy E.; Yao, Wei
Abstract: Background: One of the strongest predictors for osteoporosis is peak bone mass. Interventions to augment peak bone mass have yet to be developed. β‐Ecdysone (βEcd), a natural steroid‐like compound produced by arthropods to initiate metamorphosis, is believed to have androgenic effects and so may be used to augment bone mass. Questions/purposes: The purpose of this study was to use both male and female (1) gonadal‐sufficient; and (2) ‐insufficient mice to investigate sex differences in terms of bone development and structure after βEcd administration. Methods: Two‐month‐old male and female Swiss‐Webster mice were randomized to receive either vehicle or βEcd (0.5 mg/kg) for 3 weeks. In a separate experiment to evaluate the effects of βEcd on sex hormone‐deficient mice, gonadectomy was performed in male (orchiectomy [ORX]) and female mice (ovariectomy [OVX]). Sham‐operated and the ORX/OVX mice were then treated for 3 weeks with βEcd. Primary endpoints for the study were trabecular bone structure and bone strength. Results: In male mice, the trabecular bone volume was 0.18 ± 0.02 in the placebo‐treated (PL) and 0.23 ± 0.02 in the βEcd‐treated group (p < 0.05 versus PL); and 0.09 ± 0.01 in the ORX group (p < 0.05 versus PL) and 0.12 ± 0.01 in the ORX + βEcd group. Vertebral bone strength (maximum load) was 43 ± 2 in PL and 51 ± 1 in the βEcd‐treated group (p < 0.05 versus PL); and 30 ± 4 in the ORX group (p < 0.05 versus PL) and 37 ± 3 in the ORX + βEcd group. In female mice, trabecular bone volume was 0.23 ± 0.02 in PL and 0.26 ± 0.02 in the βEcd‐treated group (p < 0.05 versus PL); and 0.15 ± 0.01 in the OVX group (p < 0.05 versus PL) and 0.14 ± 0.01 in the OVX + βEcd group. Maximum load of the vertebrae was 45 ± 2 in PL and 48 ± 4 in the βEcd‐treated group; and 39 ± 4 in the OVX group (p < 0.05 versus PL) and 44 ± 4 in the OVX + βEcd group. Conclusions: These findings suggest the potential use of βEcd in the augmentation of bone mass in growing male and female mice. It may also partially prevent the detrimental effects of gonadectomy on trabecular bone. Clinical Relevance: Our results support the potential use of βEcd or nature products that are rich in βEcd to augment peak bone mass. βEcd may differ from the other anabolic hormone treatments that may have severe side effects such as serious cardiac complications. However, its effects on humans remain to be determined.